Neuroimage of the Subventricular Zone Associated with Intrauterine Ischemic Infarction - Ramos-Zuñiga R; Rochin-Mozqueda JA; García-Mercado CJ (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
The patient is a 5 year-old male child, product of the second gestation, in a 36 year old mother without comorbidities. During pregnancy, risk of abortion was presented since the third month of gestation and was managed with obstetrical care and rest. The product was obtained by vaginal birth at 40 weeks of gestation, presenting hypoactivity and secondarily generalized partial seizures. It was decided to initiate treatment with phenytoin. During his neurological evolution, he presented backwardness in the psychomotor development, right hemiparesia that progressed to spasticity (spastic hemiparesia), language and communication limitation, subsequently he recurred with convulsive crisis. Currently the patient is treated with levetiracetam and clonazepam, presenting appropriate control.